Measurement of civil engineering works based on the Malaysian CESMM - Sabaria Hassan (Penerbit Universiti Teknologi Mara, 2011)
The use of bills of quantities is a well-established mean of enabling the financial control and management of civil engineering works. The key to the success of the use of bills of quantities is a clear understanding by all parties to the contract of what is and is not includes, in the measurement. This gives rise of the requirement for the clearly defined standard methods of measurement, hence "Measurement of Civil Engineering Works based on the Malaysia CESMM" is created. This book is separated into two parts; methods of how to kick start doing a civil engineering taking off and the explanatory notes on Malaysian CESMM, and the other contains the worked examples. This format is adopted mainly due to the majority of the practical worked examples inevitably contain several work classes in their construction processes, whereby they could not be readily fitted into any one particular explanatory chapter.